The influence of influencer endorsement on brand awareness and brand image towards purchase intention on "lozy" fashion and hijab products - Annisa, Annisa; Kussudyarsana, Kussudyarsana (Jurnal Mantik, 2025)
This study investigates the influence of influencer endorsement on brand awareness and brand image toward purchase intention for "Lozy" fashion and hijab products. Employing a quantitative research approach, the study uses SPSS for data analysis, with primary data collected through questionnaires distributed via Google Forms. The sample is selected through purposive sampling, focusing on individuals aged 17 years or older with an interest in Lozy products. The study examines four variables: Influencer Endorsement (X1), Brand Awareness (X2), Brand Image (X3), and Purchase Intention (Y). Influencer Endorsement is assessed through reliability, knowledge, confidence, visibility, and attraction; Brand Awareness is evaluated based on recall, recognition, purchase consideration, and consumption; Brand Image is measured through brand association, favorability, and uniqueness; and Purchase Intention is gauged through transactional, exploratory, preferential, and referential interest. Statistical tests for validity, reliability, classical assumptions, coefficient of determination (R²), F-tests, and t-tests are conducted. The results reveal that brand awareness, brand image, and influencer endorsement all have a positive and significant impact on purchase intention. The study suggests expanding the scope of variables in future research to include factors such as electronic word-of-mouth (e-WOM), perceived quality, and product pricing